2003
DOI: 10.1186/1477-7525-1-46
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: It is commonly claimed that the nausea and vomiting accompanying cytotoxic chemotherapy have a negative impact on health-related quality of life. While this may seem self-evident, until a few years ago there was little empirical data demonstrating that the failure to control postchemotherapy emesis affects aspects of quality of life.In spite of their limitations, several observational studies showed that nausea and vomiting associated with chemotherapy induced a decrease in health-related quality of life with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(31 citation statements)
references
References 25 publications
2
27
0
2
Order By: Relevance
“…The total score, calculated by summing the responses to the 18 items, ranges from 18 to 126, with higher scores representing better health outcomes (i.e., less impact of CINV on daily life) [18]. Following Bloechl-Daum et al, an individual item score of six or more, and a total FLIE score of 108 or more were considered evidence of no or minimal impact of CINV on daily life [5].…”
Section: Methodsmentioning
confidence: 99%
“…The total score, calculated by summing the responses to the 18 items, ranges from 18 to 126, with higher scores representing better health outcomes (i.e., less impact of CINV on daily life) [18]. Following Bloechl-Daum et al, an individual item score of six or more, and a total FLIE score of 108 or more were considered evidence of no or minimal impact of CINV on daily life [5].…”
Section: Methodsmentioning
confidence: 99%
“…The survey, which took 10–15 minutes to complete, included the Modified Functional Living Index–emesis (M-FLIE),30,31 Functional Assessment of Chronic Illness Therapy-fatigue (FACIT-F),32 and Martin et al’s NV-5 instruments 33. The M-FLIE measures functional impact of nausea (nine items) and vomiting (nine items) on daily life; total scores range from 18 to 126, and higher scores indicate better QoL 30,31,34. The 13-item FACIT-F assesses the impact of fatigue on QoL; total scores range from 0 to 52, higher values indicate better QoL, and a ±3-point change in score from baseline is considered clinically meaningful 32.…”
Section: Methodsmentioning
confidence: 99%
“…Uncontrolled CINV can result in malnutrition, dehydration, and electrolyte imbalance [8] and has been associated with the development of anticipatory nausea and vomiting with the potential to compromise adherence to treatment [8, 9]. Fortunately, substantial progress in our understanding of the neural mechanisms underlying CINV has led to the development of highly effective therapeutic approaches [9].…”
Section: Introductionmentioning
confidence: 99%
“…Validation of the FLIE instrument is a sensitive and reliable measure of the impact of CINV on QoL [16, 17]. Furthermore, use of the FLIE has demonstrated that beyond a reduction in the physical symptoms of nausea and vomiting, effective antiemetic prophylaxis reduces the negative impact of CINV on patients’ daily lives [8, 18]. …”
Section: Introductionmentioning
confidence: 99%